Parental knowledge, attitude and practices regarding febrile convulsion - S., Srinivasa; Anjum, Syeda Kausar; Patel, Shruthi; S., Harish; G., Bhavya (International Journal of Contemporary Pediatrics, 2018)
Background: Febrile convulsion is a condition which can emotionally traumatize most parents. Inadequate knowledge regarding febrile convulsion can cause parental anxiety. This study is conducted to assess the level of parent’s knowledge, attitude and practices regarding febrile convulsion. Methods: It was a prospective questionnaire study conducted over a period of one year from January 2016 to January 2017 in Department of Paediatric of a tertiary care hospital KIMS, Bangalore. 110 children with febrile convulsion in the age group of 6 months to 5 years were enrolled. Results: Out of 110 children, 82 had single convulsion and 28 had recurrent convulsions. Mean age of onset of first febrile convulsion was 20 months. About 50 (45.45%) had experienced convulsion with one-episode of fever. Only 46 (41.8%) of parents recognized convulsion. Others interpreted convulsion as shivering (20.9%), evil effect (7.2%), excessive cry tantrum (10.9%), fainting spell (8.18%) and lethargy (20%). 88 (80%) did not carry out any intervention prior to getting the child to hospital. Effect of convulsion on parents was fear of death (82.7%), fear of epilepsy (17.3%), fear of recurrence (34.5%). 85% parents did not know that convulsion can occur due to fever. 32% thought that traditional treatment would help. Only 38% had thermometer at home and 23% knew the normal range of body temperature. Preventive measures were known to 44%. Conclusions: A higher level of understanding regarding practices was shown among higher socioeconomic and higher educational status. The efficiency of parental first aid practices can be evaluated and significant improvement can be achieved by giving adequate awareness and education.